(untitled) (PANGEEA, 2025)
ABSTRACT: A segment of railway in context of “Bivolari” rebellion. The paper with the above title captures several new aspects from the early period of the Romanian railway epic story when a riot of 503 “buffaloes”, occurred between March 18th and September 25th 1873, had delayed until 1906 the completion of 4,150 km between Giurgiu railway station and Giurgiu port. Between the agricultural workers who were mainly transporting grains from Giurgiu railway station to Giurgiu port with carts and buffaloes (hence “buffaloes”) and the wholesalers from the port, conflicts occurred regarding failed agreements, which at its peak resulted unjustified in 7 deaths, 80 arrests and other 22 detentions for over a period of six months. The situation ended legally with the release of the 22 people in detention, due to a high advocate craftsmanship of the Transylvanian revolutionary Alexandru Papiu-Ilarian (1827-1877), former Minister of Justice for 4 months in Mihail Kogălniceanu’s Administration and the first Romanian scholastic who held a welcoming speech (about the life and ideas of Gheorghe Şincai at his admission in the Romanian Academy in 1868). Although the “buffalo” guild ceased to exist after 1906, it appears that their riot represented the first form of organized struggle with a collective nature within the Romanian rural and suburban space. As an original position, the authors suggest building a monument in Giurgiu to be inaugurated on September 25th 2013, dedicated to honoring the “buffalo” riot, at 140 years distance from their unique gesture in Romanian history.